1982
DOI: 10.1042/cs0630325
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aldosterone Responsiveness to Angiotensin II during Clinical Variations in Calcium Metabolism in Normal Man

Abstract: 1. Angiotensin II was infused at stepwise increasing dose rates (2, 4 and 10 pmol min-1 kg-1) in 12 normal subjects. Infusions were performed in the presence of normocalcaemia, mild hypercalcemia induced by concomitant calcium gluconate infusion, and after 2 weeks of treatment with nifedipine. 2. Pre-infusion plasma levels of angiotensin II, renin or aldosterone were not altered by acute mild hypercalcaemia or administration of nifedipine. The angiotensin II-induced increases in plasma aldosterone were also si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…In this study, the intravenous infusion of nicardipine did not interfere with the aldosterone response. There is no conclusive evidence that long-term therapy with nifedipine inhibits the aldosterone response (Bianchetti et al, 1982;Millar et al, 1983); similarly, in this study, therapy with nicardipine for 1 week had no significant effect on the aldosterone response. It has been shown that aldosterone levels were low relative to the level of plasma renin activity during chronic therapy with nifedipine (Hiramatsu et al, 1982), but this was not confirmed in the present study with nicardipine.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In this study, the intravenous infusion of nicardipine did not interfere with the aldosterone response. There is no conclusive evidence that long-term therapy with nifedipine inhibits the aldosterone response (Bianchetti et al, 1982;Millar et al, 1983); similarly, in this study, therapy with nicardipine for 1 week had no significant effect on the aldosterone response. It has been shown that aldosterone levels were low relative to the level of plasma renin activity during chronic therapy with nifedipine (Hiramatsu et al, 1982), but this was not confirmed in the present study with nicardipine.…”
Section: Discussioncontrasting
confidence: 71%
“…However, there is evidence that nifedipine acutely diminished the aldosterone response to angiotensin II (Millar et al, 1981;Vierhapper & Waldhausl, 1982). This inhibition was not sustained during chronic therapy (Bianchetti et al, 1982;Millar et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with the previous study [29], our study shows that plasma renin activity and aldosterone levels remain unchanged after dosing with nifedipine-SR. Aldosterone synthesis in the zona glomerulosa is stimulated by angiotensin (ANG II), and nifedipine-C diminishes the response to exogenous ANG II when given acutely [30,31] but not chronically [32,33]. However, aldosterone levels during chronic administration of nifedipine-C are less than what would be expected from concurrent values for circulating renin [34].…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, Marone et al (1981) did not observe any significant change in plasma aldosterone in response to an acute hyper¬ calcaemia. In a further study (Bianchetti et al 1982), the same group reported that mild hyper¬ calcaemia induced by calcium gluconate infusion did not influence aldosterone responsiveness to angiotensin II. The sum of these partially conflict¬ ing results does not allow a firm conclusion on the influence of calcium on aldosterone secretion.…”
Section: Discussionmentioning
confidence: 95%